Desolation and enlightenment : political knowledge after total war, totalitarianism, and the Holocaust - Katznelson, Ira (University seminars/Leonard Hastings Schoff memorial lectures., 2003)
During and especially after the Second World War, a group of leading scholars who had been perilously close to the war's devastation joined others fortunate enough to have been protected by distance in an effort to redefine and reinvigorate Western liberal ideals for a radically new age. Treating evil as an analytical category, they sought to discover the sources of twentieth-century horror and the potentialities of the modern state in the wake of western desolation. In the process, they devised strikingly new ways to understand politics, sociology and history that reverberate still. In t.